Chromatography-Free Esterification Reactions Using a Bifunctional Polymer - Ma, Shuang; Toy, Patrick H. (Synlett, 2016)
A linear polystyrene functionalized with both nucleophilic DMAP groups and sterically hindered tertiary amine groups was synthesized and used homogeneously in a range of esterification reactions between alcohols and various carboxylic acid derivatives. The polymer was highly effective in such reactions where the DMAP groups served as catalytic groups. The ester products of these reactions could be isolated in high purity and yield without the need for chromatographic purification, and the polymer could be recovered and reused numerous times with no apparent decrease in utility.
Keywords: DMAP; esterification reactions; organocatalysis; polymer-supported catalysts; polymer-supported reagents